1992
DOI: 10.1111/j.1528-1157.1992.tb02206.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Felbamate in Pediatric and Adult Beagle Dogs

Abstract: The relative bioavailability and pharmacokinetics of felbamate (FBM) after a single oral dose and after 10 once-daily oral doses of 60 mg/kg were investigated in adult and pediatric dogs of both sexes. The pediatric and adult dogs were aged 4-6 weeks and 1-2 years, respectively. Analysis of variance (ANOVA) was performed on the bioavailability parameters among all groups and between the first and last doses. No sex-related differences in bioavailability and pharmacokinetic parameters were observed. The bioavai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…However, these drugs are not without risks including myelosuppression, hepatotoxicity, gastrointestinal disturbances, and other drug‐specific systemic effects; therefore, regular monitoring of complete blood counts (CBC), serum biochemistry, and where possible, effective concentrations are recommended (Viviano, ). In pediatric animals, immunosuppression poses additional challenges in part due to age‐related differences in drug metabolism, where existing safety, efficacy and toxicity data may lack accuracy when doses are extrapolated from studies in adult animals to younger immature dogs (Adusumalli, Gilchrist, Wichmann, Kucharczyk, & Sofia, ; Tassinari, Benson, Elayan, Espandiari, & Davis‐Bruno, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these drugs are not without risks including myelosuppression, hepatotoxicity, gastrointestinal disturbances, and other drug‐specific systemic effects; therefore, regular monitoring of complete blood counts (CBC), serum biochemistry, and where possible, effective concentrations are recommended (Viviano, ). In pediatric animals, immunosuppression poses additional challenges in part due to age‐related differences in drug metabolism, where existing safety, efficacy and toxicity data may lack accuracy when doses are extrapolated from studies in adult animals to younger immature dogs (Adusumalli, Gilchrist, Wichmann, Kucharczyk, & Sofia, ; Tassinari, Benson, Elayan, Espandiari, & Davis‐Bruno, ).…”
Section: Introductionmentioning
confidence: 99%
“…It also easily crossed the blood-brain barier (BBB), as was demonstrated by the above mentioned authors. The volume of distribution (Vd) of this agent was 0.9 to 1.1 L/kg (Table 2), however, in pediatric dogs the value reached 1.2-1.9 L/kg (Adusumalli et al 1992). FBM bound with plasma proteins from 22 to 25% (Table 2) and the albumin was responsible for most of the binding.…”
Section: Felbamatementioning
confidence: 99%
“…The time of maximum concentration (t max ) of FBM was reached in 4.0 to 5.5 h after the single and multiple oral dose, respectively and was not dependent on dose value. However, in pediatric dogs t max was about 3.0 h (Adusumalli et al 1992). Adusumalli et al (1991) proved that FBM is distributed readily into tissues and did not appear to accumulate in any particular tissue.…”
Section: Felbamatementioning
confidence: 99%
See 1 more Smart Citation
“…Boudinot et al (1993) reported age differences in the kinetics of piroxicam in rats. Adusumalli et al (1992), Yang et al (1992), Vermeulen et al (1992), and Rumore and Blaiklock (1992) have also reported age dependence in kinetics of drugs in humans, dogs, and rats. However, a paucity of information exists for age-dependent pharmacokinetics of pesticides.…”
Section: Introductionmentioning
confidence: 97%